2017
DOI: 10.3390/beverages3040060
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organochlorine Pesticide Residues in Some Selected Cocoa Beverages in Nigeria

Abstract: This study evaluates the quality of the cocoa beverages produced in Nigeria with respect to the occurrence and levels of organochlorine pesticides OCPs residues in order to ascertain the potential health risks to the general public. Seven cocoa-based beverages were analysed for 17 OCP residues using gas chromatography coupled with an Electron Captured Detector (GC-ECD) after extraction and silica-gel clean-up. The study reveals the presence of ten OCP residues in the cocoa beverages, with a concentration range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
2
1
2
Order By: Relevance
“…The levels of p, pʹ DDT in the cocoa samples in this study were comparable to 0.040-0.440 mg/kg and 0.010-0.110 mg/kg reported by Aikpokpodion [29] and Bempah et al, [30] respectively. Also, similar values (0.03-0.118 mg/kg) has been reported in cocoa beverages in Nigeria [26].…”
Section: Endosulfan I Endosulfan Ii and Endosulfan Sulphatesupporting
confidence: 87%
See 1 more Smart Citation
“…The levels of p, pʹ DDT in the cocoa samples in this study were comparable to 0.040-0.440 mg/kg and 0.010-0.110 mg/kg reported by Aikpokpodion [29] and Bempah et al, [30] respectively. Also, similar values (0.03-0.118 mg/kg) has been reported in cocoa beverages in Nigeria [26].…”
Section: Endosulfan I Endosulfan Ii and Endosulfan Sulphatesupporting
confidence: 87%
“…The concentrations of endosulfan I and II in some of the cocoa samples analysed were lower than ND-0.120 mg/kg and 0.040-0.110 mg/kg reported by Boakye [19] for endosulfan I and II respectively. However, the values in this study were higher than ND-0.256 mg/kg reported for endosulfan I and II in cocoa beverages in Nigeria [26]. Endosulfan I, endosulfan II and endosulfan sulphate were detected in 100%, 75% and 45% of soil samples from Oluji 1 and 2, respectively.…”
Section: Endosulfan I Endosulfan Ii and Endosulfan Sulphatecontrasting
confidence: 79%
“…The cyclodienes (heptachlor, Aldrin, dieldrin, endrin, endosulfan II) were detected to have a concentration range of (ND-0.256 mg/kg). In this study, the dichlorophenylethanes and cyclodienes are seen to be far greater than the results Ibigbami and Adeboware [37] reported with values ranging from (ND-0.25 mg/kg) and (ND-1.27 mg/kg).…”
Section: Organochlorine Pesticides Residuescontrasting
confidence: 73%
“…The order goes thus, MLT < HIM < MAG < DUB < AMS. Analysis of seven cocoa-based beverages in Nigeria for Persistent Organochlorine Pesticide Residues was carried out by Ibigbami and Adeboware [37]. Fourteen (14) samples, two samples for each brand of cocoa beverage, were purchased at a Supermarket in Ado-Ekiti, South-Western Nigeria, and the selection was based on the availability of the samples at the point of purchase.…”
Section: Organochlorine Pesticides Residuesmentioning
confidence: 99%
“…these concentrations were found to be relatively higher than the recommended 0.01 µg L -1 MRLs in drinking water [18]. Similar studies carried out in Ogbese river in Ekiti showed lower concentration of this OCPs congeners [28]. However, Ogbeide et al [29] detected higher levels than that reported in this study for HCBs and DDTs in sediments from 3 water bodies (Illushi, Ogbese, and Owan River) situated in Niger Delta, Nigeria.…”
Section: Concentrations (µG L -1 ) Of Chlorinated Benzene In the Grou...supporting
confidence: 60%